Decolonizing Vision on Borderlands: The Mexican Southern Borderlands in Critical Review. Issue 2 (3rd March 2016) - Laako, Hanna
Abstract: This article critically examines the Mexican southern borderlands, understood both as a concrete borderline region and as a concept constructed by scholars. Building on recent borderlands debates, the article constructs a decolonizing vision, which provokes us to ask: To what extent is the borderlands perspective colonialist? By dividing the world into centers and peripheries, do we automatically repeat the centrist interpretations? Are the habitants of the borderlands thinking they are living in a periphery? By exploring academic literature on Mexican southern borderlands and decolonizing criticisms set forward by the Zapatista movement, the article brings forth epistemological challenges related to colonialist imagery and vocabulary on borderlands, suggesting a decolonizing vision from which to shed a new light to the world political centers and peripheries. This way, the article attempts at bridging critical borderlands studies with the field of international relations.